2018
DOI: 10.1007/jhep09(2018)111
|View full text |Cite
|
Sign up to set email alerts
|

Non-vanishing heterotic superpotentials on elliptic fibrations

Abstract: We present models of heterotic compactification on Calabi-Yau threefolds and compute the non-perturbative superpotential for vector bundle moduli. The key feature of these models is that the threefolds, which are elliptically fibered over del Pezzo surfaces, have homology classes with a unique holomorphic, isolated genus-zero curve. Using the spectral cover construction, we present vector bundles for which we can explicitly calculate the Pfaffians associated with string instantons on these curves. These are sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
(142 reference statements)
0
5
0
Order By: Relevance
“…Recently, it has been shown that the assumptions underlying the vanishing theorems of refs. [26][27][28][29] do not necessarily apply in generic heterotic compactifications [72,73]. In the latter references, examples of non-vanishing non-perturbative superpotentials were found among both CICY and elliptically fibered CY manifolds.…”
Section: Jhep05(2021)105mentioning
confidence: 99%
“…Recently, it has been shown that the assumptions underlying the vanishing theorems of refs. [26][27][28][29] do not necessarily apply in generic heterotic compactifications [72,73]. In the latter references, examples of non-vanishing non-perturbative superpotentials were found among both CICY and elliptically fibered CY manifolds.…”
Section: Jhep05(2021)105mentioning
confidence: 99%
“…[13][14][15][16]). On the other hand, a number of papers [17][18][19][20] have produced examples with a nonvanishing W C , thus apparently evading the vanishing theorems of Ref. [12].…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [17][18][19][20][21][22][23], tools were derived that facilitate the computation of Pfaffians purely based on methods of algebraic geometry. The key observation is that the Pfaffian on some curve γ i will be zero iff the bundle…”
Section: Introductionmentioning
confidence: 99%